2016
DOI: 10.1097/mpg.0000000000001023
|View full text |Cite
|
Sign up to set email alerts
|

Functional Gastrointestinal Disorders Dominate Pediatric Gastroenterology Outpatient Practice

Abstract: More than half of new pediatric gastrointestinal clinic patients met the Rome 3 criteria for ≥1 FGIDs. Satisfying the criteria may facilitate diagnosis on the first visit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 21 publications
3
58
1
16
Order By: Relevance
“…Studies from the pediatric literature suggest the prevalence of symptoms meeting criteria for CVS in children and adolescents in the general population are between 0.3% and 1.9%, as high as 6.1% in primary care populations, and 8% to 10% in a pediatric gastroenterology clinic . The prevalence in the latter two studies among children is similar to that observed in our study in adults.…”
Section: Discussionsupporting
confidence: 87%
“…Studies from the pediatric literature suggest the prevalence of symptoms meeting criteria for CVS in children and adolescents in the general population are between 0.3% and 1.9%, as high as 6.1% in primary care populations, and 8% to 10% in a pediatric gastroenterology clinic . The prevalence in the latter two studies among children is similar to that observed in our study in adults.…”
Section: Discussionsupporting
confidence: 87%
“…Functional gastrointestinal (GI) disorders are highly prevalent, occurring in 10%–20% of population worldwide (Saito, Schoenfeld, & Locke III, ; Chang, Lu, & Chen, ; Lewis, Palsson, Whitehead, & van Tilburg, ). These disorders constitute the primary reason for GI referral in pediatric tertiary care centers (Rouster, Karpinski, Silver, Monagas, & Hyman, ) and do not respond well to gut‐targeted drug therapies (Drossman et al, ; Sobin, Heinrich, & Drossman, ). They encompass a range of problems with digestion, defecation, abdominal pain, vomiting, nausea, and swallowing without an identifiable structural pathology.…”
Section: Comorbidity Of Psychiatric and Gi Tract Pathology And Their mentioning
confidence: 99%
“…FGIDs such as IBS are frequently encountered in clinical practice, yet they are a group of disorders that elicit symptoms through an etiology that is poorly understood and currently not identifiable . Descriptive evidence demonstrates that patients feel that foods are involved in the etiology of their symptoms, and often foods containing fermentable carbohydrates are avoided in an attempt to reduce symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…Bloating, abdominal pain/discomfort, and changes in bowel function, namely stool frequency and consistency, characterize IBS. GI symptom resolution is the primary reason patients seek medical treatment . Currently, IBS in pediatric patients is diagnosed by Rome IV criteria, and was previously diagnosed by Rome III criteria (Table ) .…”
Section: Introductionmentioning
confidence: 99%